Investigation of the Effects of the Short QT Syndrome D172N Kir2.1 Mutation on Ventricular Action Potential Profile Using Dynamic Clamp - Du, Chunyun; Rasmusson, Randall L.; Bett, Glenna C.; Franks, Brandon; Zhang, Henggui; Hancox, Jules C. (Frontiers in Pharmacology, 2022)
The congenital short QT syndrome (SQTS) is a cardiac condition that leads to abbreviated ventricular repolarization and an increased susceptibility to arrhythmia and sudden death. The SQT3 form of the syndrome is due to mutations to the KCNJ2 gene that encodes Kir2.1, a critical component of channels underlying cardiac inwardly rectifying K+ current, I(K1). The first reported SQT3 KCNJ2 mutation gives rise to the D172N Kir2.1 mutation, the consequences of which have been studied on recombinant channels in vitro and in ventricular cell and tissue simulations. The aim of this study was to establish the effects of the D172N mutation on ventricular repolarization through real-time replacement of I(K1) using the dynamic clamp technique. Whole-cell patch-clamp recordings were made from adult guinea-pig left ventricular myocytes at physiological temperature. APs were elicited at 1Hz. Intrinsic I(K1) was inhibited with a low concentration (50µM) of Ba2+ ions, which led to AP prolongation and triangulation, accompanied by a ~6 mV depolarization of resting membrane potential. Application of synthetic I(K1) through dynamic clamp restored AP duration, shape and resting potential. Replacement of wild-type (WT) I(K1) with heterozygotic (WT-D172N) or homozygotic (D172N) mutant formulations under dynamic clamp significantly abbreviated AP duration (APD90) and accelerated maximal AP repolarization velocity, with no significant hyperpolarization of resting potential. Across stimulation frequencies from 0.5 to 3 Hz, the relationship between APD90 and cycle length was downward shifted, reflecting AP abbreviation at all stimulation frequencies tested. In further AP measurements at 1Hz from hiPSC cardiomyocytes, the D172N mutation produced similar effects on APD and repolarization velocity; however, resting potential was moderately hyperpolarized by application of mutant IK1 to these cells. Overall, the results of this study support the major changes in ventricular cell AP repolarization with the D172N predicted from prior AP modelling and highlight the potential utility of using adult ventricular cardiomyocytes for dynamic clamp exploration of functional consequences of Kir2.1 mutations.